Effect of friction between the steel core and concrete on the seismic performance of Buckling Resistant Brace Frames - Mahmoud reza shiravand (Iranian Society of Structrual Engineering (ISSE), 2019)
Structures with Buckling Resistant Braced Frames (BRBF) have two significant properties of energy dissipation and lateral stiffness during an earthquake. BRBF consists of steel core surrounded by a hollow steel section, coated with a low-friction material, and then grouted with a specialized mortar. The encasing and mortar Prohibit the steel core from buckling when in compression, while the coating prevents axial load from being transferred to the mortar, thus preventing strength loss and allowing for better symmetric cyclic performance .Using BRBF as a fuse element in seismic design of structures leads to reduction of structure’s weight and consequently post-earthquake repair costs. One of the main constituents of BRBF system is the unbounded material between steel core and mortar (concrete) that should not have high friction coefficient (μ). This research is focused on the effect of friction coefficient of unbounded material on the seismic behaviour of BRBF within a range of μ=0 to μ=0.3. The results showed that reduction of the friction coefficient results in a greater ductility and energy dissipation. Also, the number of load cycles applied on the structures till the Occurrence of failure, have been increased by decrease in the friction coefficient. The dissipated energy of BRBF system in the case of various friction coefficients is computed about 50%, 62%, 63%, 65%, 71% and 90%, respectively, for μ=0.3, μ=0.2, μ=0.1, μ=0.05, μ=0.025 & μ=0.01 compared to that of low friction coefficient equal to μ=0.001. It can be deduced from these paper that by reducing the friction coefficient of the unbounded material, the characteristics such as energy dissipation and ductility will be enhanced and consequently the seismic performance of the system will be improved.